2006
DOI: 10.1002/jmv.20601
|View full text |Cite
|
Sign up to set email alerts
|

The changing epidemiology of HIV/AIDS at a Minnesota hospital: Impact of demographic change and viral diversity

Abstract: The past decade has seen a dramatic influx of African-born immigrants and refugees into Minnesota. The impact of this on Hennepin County Medical Center (HCMC), a public teaching hospital located in Minneapolis, has been considerable, especially in the management of HIV-infected persons given that approximately 30% of newly diagnosed individuals seen at HCMC in the past 3 years acquired the virus in Africa. An ongoing and permanent alteration in the demographics of HIV/AIDS in this part of the American midwest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…The utility of resistance genotyping sequences for HIV-1 characterization has been established by numerous studies (23,26,(34)(35)(36)(37)(46)(47)(48)(49). Current U.S. guidelines recommend resistance genotype testing at the initiation of antiretroviral therapy and for subsequent patient monitoring (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utility of resistance genotyping sequences for HIV-1 characterization has been established by numerous studies (23,26,(34)(35)(36)(37)(46)(47)(48)(49). Current U.S. guidelines recommend resistance genotype testing at the initiation of antiretroviral therapy and for subsequent patient monitoring (50).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of increasing non-B prevalence in the United States, and it may be higher than generally recognized (29,(32)(33)(34). Although data are limited, studies have shown that the prevalence of non-subtype B varies greatly depending on the population analyzed, ranging from 0.6% in a northern California clinic-based setting (35) to 95% in African-born immigrants in Minneapolis, MN (28,36), and New York City (27). The largest published population-based study to date was performed by the Centers for Disease Control and Prevention.…”
mentioning
confidence: 99%
“…Recently published results of a targeted HIV surveillance of the African-born, HIV-infected patients attending the HIV clinic at the Hennepin County Medical Center, Minneapolis, MN, are quite dramatic [Hirigoyen and Cartwright, 2005;Sides et al, 2005;Cartwright, 2006]. The majority (95%) of African-born patients, who make up 10% of the clinic patients, were infected with non-B strains.…”
Section: Hiv-1 Non-b Strains In Usmentioning
confidence: 95%
“…Among African-born persons newly diagnosed with HIV at Hennepin County Medical Center (Minneapolis), it was estimated 70 % acquired the virus in the U.S. [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although, it is difficult to quantify the percentage of new HIV infections occurring among African-born persons in the U.S. as compared to those who acquired the infection outside the U.S., [3], many cases of HIV infections among African-born persons are thought to have been in their native countries [5]; nonetheless, many immigrants are also being infected in the U.S. [2,12]. Among African-born persons newly diagnosed with HIV at Hennepin County Medical Center (Minneapolis), it was estimated 70 % acquired the virus in the U.S. [12].…”
Section: Introductionmentioning
confidence: 99%